Legitimacy and Legitimization in Low Turnout Ballots. Issue 3 (13th January 2016) - Kirkland, Christopher; Wood, Matthew
Abstract : Declining voter turnout has been highlighted as problematic for a number of western democracies. However, in this article we argue that whether an election is seen as 'legitimate' or not depends crucially upon interpretations of the levels of turnout by elite actors. Through comparing two recent democratic ballots in the UK we demonstrate how elections with lower turnouts can come to be seen as holding more legitimacy than those with higher turnouts. The cases demonstrate, we argue, a distinction between actual legitimacy, defined as a binary concept, and the process of legitimization – a process through which the authority of an institution is discursively constructed and conferred. This suggests a new research agenda which extends beyond the current literature to focus upon how the legitimacy of a ballot is socially constructed in a broader context of unequal socioeconomic power relations.